EVALUASI HEURISTIC DESAIN ANTARMUKA (INTERFACE) WEBSITE PEMASARAN UNIVERSITAS XYZ - Destriana Widyaningrum; Lukman Hakim (Universitas Bunda Mulia, 2019)
This research was conducted to improve user comfort and maintain business strategy amid increasingly widespread e-commerce competition. The researcher evaluated the interface of the XYZ University website with the Heuristic method of Nielsen and Molich, as an approach in evaluating a human-machine system (man-machine system) related to ease of use (usability).The study was conducted by evaluating the XYZ University website marketing interface, based on ten studies related to user convenience, namely feedback, metaphor, navigation, consistency, prevention, memory, efficiency, design, recovery and help. Interfaces that correspond to the study points are recorded and sampled accordingly, as well as if there is an interface that is not in accordance with the study points, it will be recorded and examples of things that are not appropriate are taken. The results of this study are in the form of a summary of recommendations for improving the interface design of the XYZ University website. Keywords: heuristic evaluation, interface, design, website